2017
DOI: 10.18869/acadpub.jafm.73.240.26425
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Corrugated Wing in Unsteady Motion

Abstract: Delayed stall is the most dominant lift enhancing factor in insect flapping motion. Micro air vehicle operates at Reynolds number 10 4 -10 5 ; slightly higher than the insects' Reynolds number (Re). In the present research, thefocus is to investigate "stall-absent" phenomenon at Re representative of the micro air vehicles, the effect of spanwiseflow on the leading edge vortex and also to study the effect of geometry variations on the aerodynamic performance of the wing in unsteady motion. Corrugated dragonfly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Noteworthy, in this study, we did not model wing stiffness and elasticity, which is in line with numerous previous studies on the significance of corrugation in dragonfly [21][22][24][25][30][31][32][33][34], bumblebee [15,35], locust [36] and fruit fly wings [6]. These studies used rigid wings and ignored any elastic deformation during wing flapping while focusing on the aerodynamic effects of surface structure.…”
Section: Reconstruction Of Model Wingsmentioning
confidence: 78%
See 2 more Smart Citations
“…Noteworthy, in this study, we did not model wing stiffness and elasticity, which is in line with numerous previous studies on the significance of corrugation in dragonfly [21][22][24][25][30][31][32][33][34], bumblebee [15,35], locust [36] and fruit fly wings [6]. These studies used rigid wings and ignored any elastic deformation during wing flapping while focusing on the aerodynamic effects of surface structure.…”
Section: Reconstruction Of Model Wingsmentioning
confidence: 78%
“…Vortices and even stagnant air cushions may thus alter a wing's effective geometry. Trapped vortices were experimentally found in wings moving at relatively high Reynolds number [52][53], including an aerodynamic study that showed vortex trapping at Reynolds numbers between 34 000 and 100 000 but not at 3500 [33]. The latter value is at the upper end of Reynolds numbers typical for flying insects.…”
Section: Vortex Trappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previously published studies used numerical or physical wing models at various Reynolds numbers for analysis and reported that wing corrugation either improves aerodynamic performance [ 56 , 58 , 65 , 66 , 118 , 135 , 136 , 137 ] or attenuates performance [ 56 , 59 , 65 , 66 , 134 , 137 , 138 , 139 ]. Other studies that reported little or no effect of corrugation on wing performance in beetles [ 55 ], dragonflies [ 140 ], bumblebees [ 141 ], hoverflies [ 142 ], and fruit flies [ 50 ] at Reynolds numbers between 35 and 34,000. Some studies, moreover, also reported inconsistent results on the significance of wing corrugation in dragonflies [ 63 , 64 , 143 , 144 ], bumblebees [ 54 ], and a generic model [ 59 ].…”
Section: Functional Relevance Of Three-dimensional Wing Shapementioning
confidence: 99%
“…There is little difference in flow patterns between flat and three-dimensional fly wings but vortices and stagnant air cushions that are trapped in corrugation valleys of a wing may potentially improve lift production by changes in wing’s effective geometry [ 61 , 135 ]. Evidence for trapped vortices were experimentally found in wings moving at relatively high Reynolds number [ 63 , 64 ], including an aerodynamic study that demonstrated vortex trapping at the wing’s acceleration phase and at Reynolds numbers ranging from 34,000 to 10 5 , but not at 3500 [ 140 ]. The latter value is at the upper end of Reynolds numbers typical for flying insects.…”
Section: Functional Relevance Of Three-dimensional Wing Shapementioning
confidence: 99%